Electrochemical deposition of palladium nanoparticles on a boron doped diamond electrode - Vojs, Marian; Matvieiev, Oleksandr; Hatala, Michal; Šelešovská, Renáta; Vrška, Martin; Michniak, Pavol; Behúl, Miroslav; Marton, Marián (BEST Servis, 2022)
The aim of this study is to prepare palladium nanoparticles (PdNP) by electrochemical techniques (constant and pulse mode) on unique boron-doped diamond electrodes (BDDE) fabricated by a combination of large area microwave chemical vapor deposition (LA MWCVD) and screen-printing technique. By analyzing the maximum of dopamine as a representative of biomolecules, we evaluated the optimal coverage of BDDE by PdNP on the surface and determined the amplification of the effective signal. As a result, by utilizing the optimized conditions, the signal of dopamine was amplified up to 7 and 5 times for the positive pulse and constant mode, respectively. The use of PdNP modified BDDE can allow its application not only for the determination of biomolecules but also for other substances in a harsh environment.
Elektrochemická depozice nanočástic palladia na bórem dopované diamantové elektrodě
Keywords: boron doped diamond electrode; paladium nanoparticles; electrochemical characterization; eectroanalysis; bórem dopovaná diamantová elektroda; paladium nanočástice; elektrochemická charakterizace; elektroanalýza